Anxious cinephilia : pleasure and peril at the movies - Keller, Sarah (Sarah K.) (Film and culture., 2020)
"The digital revolution in contemporary movie-making has engendered a wave of cinephilia among those nostalgic for the culture of cinema and the medium of film. It has also spawned growing concerns about their future. The concept of cinephilia, Keller argues, is hardly new as technological revolutions have always brought out similar reactions in the face of change and a sense of passing (the advent of sound from silent films, color, etc.). In Anxious Cinephilia, Keller looks back at the history of cinephilia from avant-garde filmmakers in the beginning of the twentieth century to the French New Wave's love of Humphrey Bogart to contemporary critics celebrating their love of cinema. She also considers the ways in which cinephilia has embraced some of the democratic/utopic aspects of the digital revolution such as Youtube and the proliferation of GIFs. Tied to cinephilia has been the concept of cinephobia, which has centered on three interrelated areas: anxieties about being captured on film (surveillance, unattractive footage of oneself, cinema's soul-stealing dangers), anxieties about cinema's deleterious influence on audiences; and anxieties about the medium itself. Keller demonstrates that a recognition of the reciprocal relationship between cinephilia and anxiety allows an entry point into understanding the current digital revolution and the history of film. Keller examines the ways in which films have depicted or thematized anxious cinephilia as well as considering audience and critical reactions to cinema and changes in film technology and culture"--